Dilemma of Medical Graduates in Nepal - Lamichhane, J (Journal of Nepal Health Research Council, 2011)
The medical education system is in infancy in Nepal. There are many constrains at various levels. The numbers of medical colleges are increasing every year without considering for its quality by the concerned authorities. Nepal Medical Council is the authorized body to look for medical professionals in the country. Even though, efforts have been made from various sectors but are insufficient. This article will mainly focus on the life of a medical graduate in Nepal. It will give an idea of how these graduates have to undergo various problems regarding their career, family, profession and social lives, right after their graduation. Â  Key words: career, dilemma, graduate, medical education, Nepal, profession